Performance of Grade 8 Students in Mathematics Intervention Program - Francisco, Jeanalyn G.; Alova, Chard Aye R.; Alova, Iana Menzi C.; Apohen, Sharon L. (Future Science / FSH-PH Publications, 2022)
Mathematics interventions are being provided for students nationwide who perform below basic on various assessments. The assessment of students’ performance in Mathematics gave rise to the conduct of this study. In this research, Grade 8 students who did not meet the expected competencies will have the opportunity to receive extra Mathematics assistance. Hence, this study is proposed so as to support the sustainability of Mathematics intervention program. This study is an action research utilizing survey questionnaire in order to determine the performance of the students in the pre- and post-tests of students under the Mathematics intervention program. The subject and the respondents of this study are the identified students in the Grade 8 who have not met the required competencies in Mathematics subject. Result showed that post-test result (Tutorial: 18.151±5.548; Remedial: 18.944±5.395) is higher than the pre-test result (Tutorial: 11.019±4.144; Remedial: 11.519±3.565) under tutorial program and remediation program. Result of the study also revealed that there is a significant difference between the performance of the students in the pre and post-test under tutorial program (t=-11.632, p=0.000) as well as in the performance of the students under remediation program tutorial program (W=0.000, p=0.000). Indeed, the aforementioned program is effective to improve the performance of students in Mathematics. Mathematics intervention program is effective to improve grades and performance of students, thus teachers should design a more improved techniques of this program.